Hydrogen Generation from Catalytic Reforming of Paraformaldehyde and Water by Polymeric Bifunctional Catalysts Comprising Ruthenium and Sulfonic Acid Units. Issue 8 (4th August 2020) - Shen, Yangbin; Bai, Chuang; Zhan, Yulu; Ning, Fandi; Wang, Huihui; Lv, Guojun; Zhou, Xiaochun
Abstract: As a clean and sustainable source of energy, hydrogen shows great potential to be the ultimate energy source in future. In this research, paraformaldehyde is used as hydrogen carrier. Several bifunctional catalysts are prepared for the hydrogen generation from paraformaldehyde. The bifunctional catalysts contain two catalytically active sites. One is a sulfonic acid group for paraformaldehyde hydrolysis, and the other is an organometallic group that catalyzes the hydrogen release from formaldehyde. Bifunctional iridium catalysts and bifunctional rhodium catalysts could only generate traces of hydrogen in the initial phase of paraformaldehyde decomposition. Only the bifunctional ruthenium catalyst shows high activity due to its bifunctional catalytically active sites, thus more than 98.0 % of the initially produced gas contains hydrogen. The initial TOF is 685 h −1 at 363 K when the paraformaldehyde concentration is 20 wt%. A reaction mechanism is proposed for the hydrogen generation from paraformaldehyde in which formaldehyde and formic acid are intermediates Formic acid decomposition is the rate‐determining step in the later phase of paraformaldehyde decomposition. Abstract : The bifunctional ruthenium catalyst is developed for hydrogen generation from paraformaldehyde. Attributing to the synergistic effect of the sulfonic acid and Ru( p ‐cymene) on the bifunctional ruthenium catalyst, the catalyst has high activity for hydrogen generation from paraformaldehyde. The TOF is up to 685 h −1 at 363 K. Formaldehyde and formic acid are reaction intermediates. This research puts forward a new scheme for hydrogen generation using solid polymers. Shen, Zhou et al. report hydrogen generation from catalytic reforming of paraformaldehyde and water by polymeric bifunctional catalysts comprising ruthenium and sulfonic acid units.